Hydrogel Delivery System Containing Calendulae flos Lyophilized Extract with Chitosan as a Supporting Strategy for Wound Healing Applications - Justyna Chanaj-Kaczmarek; Magdalena Paczkowska; Tomasz Osmałek; Barbara Kaproń; Tomasz Plech; Daria Szymanowska; Marta Karaźniewicz-Łada; Joanna Kobus-Cisowska; Judyta Cielecka-Piontek (MDPI AG, 2020)
Calendulae flos is a valued plant material with known anti-inflammatory and antimicrobiological properties. The limitation for its use in the treatment of chronic wounds is the lack of adhesion to the required site of action. Obtaining the Calendulae flos lyophilized extract from water-ethanolic extract allowed to prepare valuable material whose biological activity in the wound healing process was confirmed by a positive result of the scratch test. The Calendulae flos lyophilized extract was standardized for the contents of the chlorogenic acid and the narcissin. The significant potency of the Calendulae flos pharmacological activity has become the reason for studies on its novel applications in combination with the multifunctional chitosan carrier, to create a new, valuable solution in the treatment of chronic wounds. The use of chitosan as a carrier allowed for the controlled release of the chlorogenic acid and the narcissin. These substances, characterized by prolonged release from the chitosan delivery system, were identified as well permeable, based on the results of the studies of the parallel artificial membrane permeability assay (PAMPA Skin) a model simulating permeability through membrane skin. The combination of the Calendulae flos lyophilized extract and the chitosan allowed for synergy of action towards hyaluronidase inhibition and effective microbiological activity. Optimization of the hypromellose hydrogel preparation ensuring the required rheological properties necessary for the release of the chlorogenic acid and the narcissin from the chitosan delivery system, as well as demonstrated antimicrobial activity allows indicating formulations of 3% Calendulae flos lyophilized extract with chitosan 80/500 in weight ratio 1:1 and 2% or 3% hypromellose as an important support with high compliance of response and effectiveness for patients suffering from chronic wounds.